PENINGKATAN LITERASI INVESTASI GEN Z MELALUI EDUKASI TRADING EMAS BERBASIS ANALISIS TEKNIKAL DAN FUNDAMENTAL - Saputra, Riko Ferdian; Kurniasari, Irma (Gapenas Publisher, 2025)
In today's world, when the world's economic challenges are increasingly complex, it is very important for Gen Z to increase their investment literacy to become smarter in investing. Therefore, the purpose of this devotion is to create and implement a gold trading education program based on fundamental and technical analysis that is focused on improving Gen Z's investment understanding and skills. The findings of this study show that the participants have a better understanding of gold investment and make investment decisions with greater confidence. As a result, the study is expected to provide financial literacy to Gen Z and encourage them to become confident and assertive investors in the future.